ANALYSIS OF STUNTING SYMPTOMS IN EARLY CHILDHOOD WITH CLASSIFICATION TECHNIQUES (Jurnal Ipteks Terapan, 2024)
WHO estimates that the total number of disease cases that occur at a certain time in an area (prevalence) of Stunting (dwarf toddlers) throughout the world is 22 percent or 149.2 million people in 2020. In Indonesia, based on data from the Asian Development Bank, in In 2022, the percentage of prevalence of stunting among children under 5 years of age in Indonesia will be 31.8 percent. This number causes Indonesia to be in 10th place in the Southeast Asia region. Furthermore, in 2022, based on data from the Ministry of Health, Indonesia's stunting rate has decreased to 21.6 percent. According to the World Health Organization (WHO), stunting is a growth disorder in children due to poor nutrition, recurrent infections and inadequate psychosocial stimulation. The classification method is used to group factors that greatly influence the incidence of stunting in children. Using the C.45 Algorithm, this research found the main factors that can influence children's growth capacity at an early age. By using 7 attributes, namely nutritional status, age, gender, poor status, weight, height, category and obtained an accuracy rate of 88%. This study was able to produce an average accuracy value of 97.87% using 10-fold cross validation